Glimpses of Arab observations of comets - Abdel Hamid, Qusay Asaad (Al-Adab Journal, 2021)
The first result of the research was that the Arab and Muslims civilization was open to all nations, and lights the way to all other civilizations in the field of orbit observations, and continued even after the Mongolian occupation to Baghdad in (656 AH / 1258 AD).The Research found that there is a coincidencebetween what Arab and Muslim scientists results reached in orbit science with the results reached by the modern European and western scientists.The observations made by Arab and Muslim scientists eliminate all people fear from the appearance of some stars and fireballs in sky, which linked to legends. Also the research showed the accuracy of the Arab and Muslim scientists in observations the orbit, with detailed information including the day, the month and the year to the Phenomena.